2022
DOI: 10.1128/spectrum.00225-22
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Responses of Rhizosphere Fungi of Scutellaria tsinyunensis , an Endangered Plant in Southwestern China

Abstract: Our study highlighted the importance of rhizosphere fungal communities in an endangered plant, S. tsinyunensis . Comparative analysis of soil samples in nearly all extant S. tsinyunensis populations identified that soil properties, especially soil water content, might play essential roles in the survival and expansion of S. tsinyunensis .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Phenylacetaldehyde in this study was positively correlated with the bacteria of Gaiellaceae and the fungi of Tausonia , Tuber in this study. Tausonia was reported as a key species in the rhizosphere fungal network of Scutellaria tsinyunensis and was usually found as a soil‐borne pathogen from woody plants (Zuo et al, 2022). Additionally, Gaiellaceae (Bazany et al, 2022; Poudel et al, 2016) and Tuber (Flores et al, 2002) were demonstrated to defend against pathogenic microorganisms and were closely related to plant health.…”
Section: Discussionmentioning
confidence: 99%
“…Phenylacetaldehyde in this study was positively correlated with the bacteria of Gaiellaceae and the fungi of Tausonia , Tuber in this study. Tausonia was reported as a key species in the rhizosphere fungal network of Scutellaria tsinyunensis and was usually found as a soil‐borne pathogen from woody plants (Zuo et al, 2022). Additionally, Gaiellaceae (Bazany et al, 2022; Poudel et al, 2016) and Tuber (Flores et al, 2002) were demonstrated to defend against pathogenic microorganisms and were closely related to plant health.…”
Section: Discussionmentioning
confidence: 99%
“…Among the top 20 dominant fungal genera ( Table S23 ), the genus Russula was only detected in AF, while Cladosporium , Microthyrium , and Cladobotryum were only detected in AA. It is reported that some members of Russula are important ectomycorrhizal fungi that play a key role in soil nutrient uptake and cycling [ 46 ]. Also, the genus Cladobotryum has been considered a great potential antifungal resource against fungal phytopathogens [ 47 ], and its secondary metabolites displayed chemical and bioactive diversity [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, altitude was the third important environmental factor controlling the distribution of three Fritillaria species, accounting for 24%, 8% and 24.6% overall contribution to F. delavayi , F. taipaiensis and F. wabuensis , respectively. The accumulation of metabolites and nutrients in underground and subaerial organs are influenced by altitude usually interacting with the availability of nutrients, water content 71 , temperature, ultraviolet intensity, CO 2 concentration and UV-B 33 . For instance, the reproductive success of F. delavayi was critically affected by the temperature and ultraviolet intensity, and as a result, F. delavayi was distributed in a narrow altitude area 57 .…”
Section: Discussionmentioning
confidence: 99%